Outcome Quality of Inpatient and Day-Clinic Treatment in Child and Adolescent Psychiatry-A Naturalistic Study - Leonhard Thun-Hohenstein; Franka Weltjen; Beatrix Kunas; Roman Winkler; Corinna Fritz (MDPI AG, 2021)
Background: Child and adolescent psychiatry has only recently been established as a separate specialty and is practiced in different settings. The epidemiology of psychological problems in childhood is high and varied, thus qualitative work is essential. Assessment of outcome as part of quality management is central to assure the service of psychiatric care to be effective. Method: Over a three-year period consecutively admitted patients from inpatient and day-clinic treatment were prospectively evaluated. A total of 200 from 442 patients (m = 80, f = 120; age 15.1 ± 2.8 y) agreed to participate. Patients, caregivers, and therapists answered a range of questionnaires to provide a multi-personnel rating. Questionnaires used for outcome assessment were Child Behavior Checklist (CBCL) and Youth-Self-Report (YSR) (at admission, discharge, and 6 weeks after discharge) and the problem score of the Inventory of Quality of Life for children (ILK), treatment satisfaction, and process quality by the Questionnaire for Treatment Satisfaction (FBB, at discharge) and as real-life outcome control assessment of quality of life (ILK) was added (admission, discharge, and 6 wks after discharge). Results: There was a significant reduction in psychopathologicalsymptoms (CBCL, YSR) and in the problem score. Furthermore, there was a significant increase in quality of life. QoL score and YSR/CBCL scores returned to normal levels. Treatment satisfaction was high and so was satisfaction with process quality. Factors significantly influencing outcome were severity of disease and the relationship to the therapist. No differences were found for gender and setting. Conclusion: The quality management analysis revealed significant improvements of symptom load, a significant increase in QoL and a high treatment satisfaction. Furthermore, process quality was scored highly by parents and therapists.